Analisis Pembentukan Portofolio Optimal dengan Metode Stochastic Dominance dan Single Index Model Pada Saham Industri Real Estate and Property diBursa Efek Indonesia - Eftika Riya Ningrum; Yuni Utami (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
This study aims to see whether there is a difference between the stochastic dominance method and the single index method in forming an optimal portfolio. And see which method is more optimal. The sample used in the study was a real estate and property company listed on the IDX period (2013 -2017) using purposive sampling and analysis sampling techniques using the average difference test. After being tested with each method both modelstochastic and single index model, the results showed that there were differences in returns from the formation of an optimal portfolio with the test results which obtained the results of 0.048 under a significant level of 0.05. And the results of the portfolio return calculation formed by the stochastic method smaller 0.0079 than the portfolio return formed by the single index method of 0.0173 which means that the single index method is more optimal than the stochastic method.